A review of current data to support decision making for introduction of next generation higher valency pneumococcal conjugate vaccination of immunocompetent older adults in the UK. (3rd October 2021) - Vyse, Andrew; Campling, James; Czudek, Carole; Ellsbury, Gillian; Mendes, Diana; Reinert, Ralf-Rene; Slack, Mary
ABSTRACT: Introduction: The burden of pneumococcal disease in older UK adults remains substantial. Higher valency pneumococcal conjugate vaccines (PCVs) are currently in development with adult formulations for two of these anticipated to become available in 2022. This article collates and reviews relevant candidate data now available that may be used to support cost effectiveness assessments of vaccinating immunocompetent UK adults aged ≥65-years with PCVs. Areas covered: This article uses published data from surveillance systems, randomized controlled trials and observational studies. It focuses on local data from the UK but where these are either limited or not available relevant global data are considered. Expert opinion: The body of relevant data now available suggests the UK is well placed to assess the cost effectiveness of vaccinating immunocompetent ≥65-year olds with new generation higher valency PCVs. Recent contemporary data provide important new and robust insights into the epidemiology of pneumococcal disease in older UK adults and help to address much of the uncertainty and data gaps associated with previous analyses. Using these data to make informed decisions about use of new higher valency PCVs for routine use in older adults will be important for public health in the UK.